THE TOTOP SOBLUK GEGER SALVATION TRADITION IN PENDALUNGAN PROBOLINGGO COMMUNITY - Mariyatul Qibtiyah; Nur Laili; Sami'ul Mubarrok; Sultan Muhammad Saddat (Program Studi Bahasa Inggris, Universitas Panca Marga, 2023)
This research focuses on the Totop Sobluk Geger salvation tradition found in the Pendalungan Probolinggo community. The aim of this research is to describe the Totop Sobluk Geger salvation tradition found in the Pendalungan Probolinggo community. The method used in this research is a descriptive qualitative method. The data collection techniques used in this research are observation, interviews and documentation techniques. Based on the research carried out, it was found that the Totop Sobluk Geger salvation tradition is a salvation tradition that is still being preserved in the Pendalungan Probolinggo community. This tradition is a syncretistic tradition because it combines elements from Pendalungan culture and elements contained in the Islamic religion.